Challenges in Sustainability Auditing: Measuring Environmental and Social Impacts in Modern Enterprises - Sari, Ratna (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study explores the challenges and opportunities in sustainability auditing, explicitly focusing on measuring environmental and social impacts in modern enterprises. It seeks to address critical gaps in data consistency, standardized metrics, and the integration of advanced technologies and methodologies in sustainability practices. Research Design and Methodology: The study employs a Systematic Literature Review (SLR) approach to analyze existing academic literature and synthesize theoretical and practical insights. This method enables a comprehensive evaluation of current frameworks, methodologies, and technological applications in sustainability auditing, focusing on their strengths and limitations. Findings and Discussion: The research identifies significant barriers in sustainability auditing, including inconsistent data quality, a lack of global standards, and the qualitative complexities of measuring social impacts. Advanced methodologies such as Life Cycle Assessment (LCA) and Social Return on Investment (SROI) are highlighted as promising tools to address these challenges. Technologies like blockchain, artificial intelligence, and IoT are also emphasized for enhancing accuracy, transparency, and efficiency. The findings underscore the importance of integrating sustainability auditing into corporate strategies to foster stakeholder trust, improve accountability, and achieve competitive advantages. Implications: This study contributes to the theoretical understanding of sustainability auditing by bridging methodological gaps and practical challenges. Its managerial implications encourage organizations to adopt innovative tools and align auditing practices with broader sustainability goals. Additionally, policymakers are urged to support these efforts through targeted incentives and the promotion of global standards. These findings provide actionable insights for practitioners, academics, and policymakers to advance sustainability practices.